Microstructural investigation on friction stir welded AA6063 pipe. (2022) - Yadav, Jitendra; Choudhary, Prashant; Yadav, Nitish; Kumar Singh, Pranav; Gupta, Naman; Bansal, Kush; Gangil, Namrata; Noor Siddiquee, Arshad
Abstract: Friction stir welding (FSW) is a solid-state joining technique that has came out as an excellent welding technology for almost all difficult to weld materials and for various weld joint configurations. However, pipe welding remains very challenging due to low contact surface area between the tool and pipes to be welded. In the present work, FSW was carried out on AA6063 aluminium pipes using high speed steel tool of tapered cylindrical tool pin geometry. During experimentation, the rotational speed of 1120 rpm was used while the pipes were rotated at a speed of 1.57 mm/s. Two passes of FSW were performed to weld the pipes and their effect were investigated on the microstructural evolution and the microhardness. The microstructural examination revealed the big sized tunnel defect in the cross-section of welded region in one pass welded sample. With repeated/second pass on the pipe the tunnel size was substantially reduced. Microstrucral characterization confirmed the presence of all characteristically different regions of FSW with refined and equiaxed grain structure in stir zone. Microhardness profile for both samples shows similar trend.